Predation of the hooded skunk, Mephitis macroura, by the great horned owl, Bubo virginianus, in the Barranca de Metztitlán Biosphere Reserve, Hidalgo, México - Sánchez-Rojas, Gerardo; Zepeda-Hernández, Zeltzin K.; Hernández-Melo, Juan A.; Maciel-Mata, Carlos A.; Hernández- Silva, Dante A. (Therya Notes, 2021)
Documenting and describing natural history events such as predation contribute to better understand the ecological responses of species. This note describes the predation of a hooded skunk individual, Mephitis macroura, by the great horned owl, Bubo virginianus, based on video recording and photographs. Audiovisual materials were obtained as part of the camera-trap sampling of carnivorous mammals in the Barranca de Metztitlán Reserve during August–December 2016. Camera traps record the time and date of events, thus allowing an accurate recording of the interactions between the owl and the skunk individuals. Three photographs and two 10-second videos were examined. One of the videos recorded the skunk vocalization upon being attacked by the owl. The entire second video shows the inert skunk. The two species could be accurately identified on the photographs. Skunks display an aposematic coloration that is usually a highly effective camouflage to hide from terrestrial predators. However, this seems to be ineffective against nocturnal birds of prey. Owls are probably the main regulators of skunk populations. This record shows that such interaction is maintained even at the southernmost end of the distribution range of the two species.